2019
DOI: 10.5194/bg-16-4535-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of dissolved organic matter and its optical characteristics in small low and high Arctic catchments

Abstract: Abstract. Climate change is affecting the rate of carbon cycling, particularly in the Arctic. Permafrost degradation through deeper thaw and physical disturbances results in the release of carbon dioxide and methane to the atmosphere and to an increase in lateral dissolved organic matter (DOM) fluxes. Whereas riverine DOM fluxes of the large Arctic rivers are well assessed, knowledge is limited with regard to small catchments that cover more than 40 % of the Arctic drainage basin. Here, we use absorption measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 78 publications
(133 reference statements)
4
35
1
Order By: Relevance
“…In areas of boreal forest, the frost-free period is extended and the surface water can be in contact with soil carbon for a longer time resulting in higher DOC concentrations in boreal lakes. Previous studies confirm that vegetation is an important driver for DOC in permafrost catchments (Harms et al, 2016;Coch et al, 2019). Coch et al (2019) found higher DOC concentrations in moss and plant rich Low Arctic catchment on Herschel Island in Northwest Canada compared to a High Arctic catchment at Cape Bounty, Northeast Canada.…”
Section: Ecoregion Zonation As Key Factor For Pan-arctic Lake Docmentioning
confidence: 68%
See 3 more Smart Citations
“…In areas of boreal forest, the frost-free period is extended and the surface water can be in contact with soil carbon for a longer time resulting in higher DOC concentrations in boreal lakes. Previous studies confirm that vegetation is an important driver for DOC in permafrost catchments (Harms et al, 2016;Coch et al, 2019). Coch et al (2019) found higher DOC concentrations in moss and plant rich Low Arctic catchment on Herschel Island in Northwest Canada compared to a High Arctic catchment at Cape Bounty, Northeast Canada.…”
Section: Ecoregion Zonation As Key Factor For Pan-arctic Lake Docmentioning
confidence: 68%
“…Previous studies confirm that vegetation is an important driver for DOC in permafrost catchments (Harms et al, 2016;Coch et al, 2019). Coch et al (2019) found higher DOC concentrations in moss and plant rich Low Arctic catchment on Herschel Island in Northwest Canada compared to a High Arctic catchment at Cape Bounty, Northeast Canada. In our database we found high lake DOC concentrations in the boreal forest regions of Interior Alaska which are dominated by white and black spruce (Halm & Griffith, 2014).…”
Section: Ecoregion Zonation As Key Factor For Pan-arctic Lake Docmentioning
confidence: 68%
See 2 more Smart Citations
“…Percolation and the leaching of older and more degraded DOM from deeper in the soil would explain both observations. Changes in SUVA can be linked to changes in source and age of DOM (Stedmon et al, 2011;O'Donnell et al, 2014;Coch et al, 2019) and can indicate the intensity of permafrost degradation within the catchment (Abbott et al, 2014). Furthermore, direct relationships are found between dissolved organic δ 14 C and SUVA (Neff et al, 2006;Butman et al, 2012;O'Donnell et al, 2014).…”
Section: Drivers Of Seasonal Variability In Hydrochemistry and Dommentioning
confidence: 99%